ASSESSMENT OF THE STATUS OF TUBERCULOSIS MULTIDRUG-RESISTANCE (MDR-TB) IN ABU-ANGA TB REFERENCE HOSPITAL, SUDAN 2015 - 2021 (Proceedings of the Global Public Health Conference, 2023)
Scarce information is available regarding the incidence, prevalence, diagnosis, and management outcomes of Multi Drug Resistant-Tuberculosis (MDR-TB) in Sudan.. This study aimed to assess MDR-TB diagnosis, management, treatment outcomes and predictors of treatment in Abu-Anga TB Reference Hospital in Sudan between the period 2015 - 2021. A retrospective facility-based study was conducted on the records of 60 patients with MDR-TB. Twenty three patients with complete file records were enrolled in the study. Data collected from the hospital registry of the 23 MDR-TB case files was analyzed using (SPSS. Ver 24). Descriptive analysis was also used for counts percentages. Results of the study participants showed that among the 23 patients, multiple drug resistance type had the highest percentage (39.1%), Rifampicin resistance was (21.7%), poly-drug resistance represented (26%) with the Pre-XDR percentage (8.7%) and XDR types being at the lowest percentages (4.3%). The outcome of the treatment indicated that 10 patients (43.4%) were cured, 6 patients (26%) were lost to follow up, 4 patients (17.4 %) failed treatment, and 3 (13%) patients died. The findings of this study indicated that good outcome predictors were the adoption of Directly Observed Treatment Strategy, hospitalization treatment model, and in-patient treatment with family support. Poor treatment outcomes were significantly related to rural residency, HIV (human immunodeficiency virus) co-infection, and treatment relapse. It is recommended to increase patient awareness among those living in rural areas to available treatment regimens and improve disease perception to increase treatment compliance and adherence. The study findings highlighted the importance of training of health providers on the proper recording and maintenance of all MDR-TB case files.
Keywords: Tuberculosis; Multidrug resistance; Directly Observed Treatment Strategy; Treatment outcome